HYPOLIPIDIMIC AND ANTI-DIABETIC EFFECTS OF PUFA EXTRACTS FROM SARDINELLA LONGICEPS AND SARDINELLA FIMBRIATA ON ALLOXAN INDUCED DIABETIC MICE - CHITRA SOM.R.S; Raji, Laila; C.K.RADHAKRISHNAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective:Â TheÂ aimÂ ofÂ theÂ presentÂ studyÂ wasÂ toÂ investigate and compare the hypolipidimic and anti-diabetic effects along with Omega-3 fatty acid content of fatty acid extracts from two species of fishes, Sardinella longiceps and Sardinella fimbriata. Methods:Â PUFA extracts from the two species were administered on two separate sets of alloxan-induced diabetic mice subjects and various bio-chemical parameters estimated across a period of one-month and at one week intervals. A control set without inducing diabetes and another alloxan-induced diabetic-control set without administering any PUFA extracts were also kept. Bio-chemical profiles were compared against the two control sets for estimating the effects of extracts. The same extracts were subjected to gas chromatography for its quantitative analysis of the Omega-3 fatty acids. Results:Â Sets administered with PUFA extracts of both species of fishes showed significant recovery in parameters like Total Cholesterol, Triglycerides, Creatinine, LDL Cholesterol and HDL Cholesterol. Sets administered with PUFA extracts from S. fimbriata showed remarkably higher recovery as compared to S. longiceps. GC analysis showed higher concentrations of DHA in the extracts from S. fimbriata as compared to S. longiceps. Conclusion:Â Higher hypocholesterolemic effect of S. fimbriata can be attributed to its higher DHA content while its higher hypotriglyceridimic effect may be due to the combined action of DHA and EPA. Better recovery in creatinine levels for S.fimbriata extract indicates a potentially greater effect for DHA in renal functioning.Â Keywords:Â PUFA, DHA, EPA, Diabetes, Sardinella fimbriata, Sardinalla longiceps